Perancangan Sistem Penjualan Spare Part Dan Service pada Bengkel Kebumen Motor - Rosselin Rosselin; Tri Yani Akhirina; Nurfidah Dwitiyanti (Jurnal Riset dan Aplikasi Mahasiswa Informatika (JRAMI), 2021)
Bengkel Kebumen Motor is a business that is engaged in the sale of spare parts and motorcycle service services. Bengkel Kebumen Motor provides a variety of maintenance, repair and sales of spare parts as well as providing optimal service for customers. The purpose of this study is to design a spare parts and service sales system that can simplify the spare part sales process and manage service data to be faster, more effective, and efficient. The research method used in designing the spare parts and service sales system at the Bengkel Kebumen Motor is Research and Development (R&D) and the system development uses the waterfall method. Meanwhile, the data collection techniques used include interviews, observations, and conducting library research that is relevant to the spare parts and service sales system. The result of this research is the design of a computerized system built using the Java Netbeans programming language using the MySQL database. By using a computerized system, it makes it easier for workshop employees to record transactions, make it easier for the workshop to find out the amount of spare parts stock, the reporting process can be done quickly and accurately